Sistem pakar untuk menentukan penyakit pada tanaman cokelat - Susanti, Ririn; Jusak, Jusak; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
The low quality of the chocolate in Indonesia is because the cocoa plantations in Indonesia are always threatened by pests and plant diseases. Insect pest species whose numbers are greatest for cocoa crop in Indonesia for more than 130 species. This resulted in a lot of brown plants that could have been saved to die and decrease the quality of the chocolate. If this is allowed to continue, then it will impact on the level of productivity of the cocoa plant.Based on the above, the cocoa plantations requires an expert system which can provide information about diseases that attack plants brown and provide solutions to deal with the disease. This expert system application aims to help growers determine the type of chocolate for the disease being attacked by the brown plant disease symptoms are visible and also with the application of expert system, can generate solutions to deal with brown plants are diseased, so many chocolate plant are saved and it can increase production and also quality.Application of expert systems with rule-based system using forward chaining methods to help the cocoa plantations in order to know the type of disease that is attacking the brown plant based on the symptoms of the disease are seen.Keyword: Technology, forward chaining, Expert, Chocolate